Effects of conflict, displacement, and migration on the health of refugee and conflict-stricken populations in the Middle East - Selma Nouri (Intelektual Pustaka Media Utama, 2019)
The global refugee crisis has reached an all-time high, with over 68 million innocent people forced to flee their homes due to violence, famine, governmental instability, or genocide. As a result of the struggles and traumas encountered by war and migration, millions of refugees suffer from acute and life-threatening physical and mental health illnesses. However, these diseases and internal-battles are often overlooked, leaving most conflict-stricken countries and refugee camps ill-equipped and unable to cope. Rather than settling into more humane and healthy living conditions, upon migration, most refugees are faced with realities that deny them a dignified and fulfilling life. More often than not, refugee camps and host countries accommodate a deplorable lifestyle that provides minimal and inadequate health-care, extreme and life-threatening poverty, and inhumane and unsanitary living conditions-exasperating the rate and risk of morbidity and mortality amongst refugee populations. This research paper aims to analyze the harsh conditions that refugees and conflict-stricken populations are currently forced to endure, as well as the effects of those conditions on the spread of communicable and non-communicable diseases, the development and growth of neonatal disorders, and the overall rise in mental illness. The paper also aims to suggest specific measures that can be taken in order to prevent the increase in morbidity and mortality rates amongst vulnerable refugee populations and recommend steps that international bodies and non-governmental organizations can take in order to solve the refugee health crisis.